Physical Activity as a Determinant of Subjective Happiness - Ceyhun Alemdag; Serdar Alemdag; Abdullah Bora Ozkara (Lithuanian Sports University, 2018)
Background. It is clear that happiness is the aim for individuals living in a highly demanding society. Although much behaviour may result in perceived subjective happiness, it is thought that physical activity is one of such factors. In this respect, the aim of this study was to investigate participants' subjective happiness as a result of their level of the amount of exercise they take part in, as well as other secondary measures (gender, body mass index, sports facilities and sports participation of family members). Methods. The study sample consists of 312 undergraduate students (114 females, 198 males). Exercise Stages of Change Questionnaire (ESOCQ) and Subjective Happiness Scale (SHS) were used as a data collection tool in the study. Data was analyzed using the one-way analysis of variance (ANOVA), Kruskal-Wallis H test, T-test and Chi- Square (χ 2 ) test. Results.  The  results  indicated  that  subjective  happiness  of  undergraduate  students  was  dependant  on  how physically active they were, particular in males, with normal body mass index and also those who were members of sporting facilities and whose parents were also physically active. Conclusion. This study showed that university students who participated in physical activity showed subjectively higher levels of perceived happiness. Furthermore, the factors determining these relationships were supported by gender, body mass index, sports facilities and whether or not their close family members were also physically active. Keywords:  exercise, wellbeing, university students